An Empirical Spatial Accessibility Analysis of Qingdao City Based on Multisource Data - Ge Gao; Zhen Wang; Xinmin Liu; Tongfei Li (Journal of Advanced Transportation)
Accessibility could reflect people’s travel convenience, cities’ livability and sustainability, and reduce the negative impacts on the environment and safety. It is therefore a key concept in city sustainable development policies across the world. Based on the multi-source data, this paper tries to have an empirical analysis on the urban accessibility of Qingdao city from the angles of spatial linkage strength, job-hosting ratio and distributions of large-scale hospitals and schools. The multisource data includes navigation data, location based service (LBS) data, Point of Interest (POI) data and the census data. The inter-city linkage strength and internal-external linkage strength are used to evaluate the spatial linkages of the urban agglomeration. Results show that the spatial connectivity and public facilities have a very strong positive correlation with the inter-city accessibility. Meanwhile, providing transport infrastructure and services could greatly strengthen the accessibility between two areas. Job-housing ratio is used to analyze the distribution of residents and jobs. Results show that the job-housing ratio declines gradually from the central urban areas to the surrounding areas. Distributions of large-scale hospitals and schools are used to estimate the service capacity of public facilities. Results show that public service facilities are mainly concentrated in the developed areas. On the contrary, the other areas developed slowly due to lack of supporting service facilities.